Forests serve vulnerable groups in times of crises: improved mental health of older adults by individual forest walking during the COVID-19 pandemic - Kiki Ekiawan Lamatungga; Magdaléna Pichlerová; Júlia Halamová; Martin Kanovský; Dhanalakshmi Tamatam; Daniela Ježová; Viliam Pichler (Frontiers in Forests and Global Change, 2024)
Understanding the effects of environment on the mental health of older adults is crucial in an aging society. Previous research concerning restorative benefits of forests almost entirely omitted older adults as the primary target group and typically involved group forest visits, which were largely restricted during the COVID-19 pandemic. Here we investigated the effects of individual walks on the mental health of adults aged 60 years or older (N = 54). A randomized parallel intervention study was conducted with one group walking in forests and the other in built-up city centres. Each participant completed eight individual 40-min walks during 1 month. Significant improvements in cognitive flexibility and heart rate variability (HRV) as an autonomic nervous system functioning indicator were established in the forest-walking group. The relationship between HRV and environment was modulated by ambient temperature. The study shows that access to forests during crises can support mental health of older adults as a vulnerable demographic.